Peningkatan Keterampilan Berbicara Melalui Proses Penerapan Metode Bermain Peran Siswa Kelas IV SDNegeri 03 Merigi Semester I Tahun 2015/2016 - Latifah, Latifah (Jurnal PGSD, 2018)
This research attempted to study the problem of (1) How to improve the skill of V grade students of Primary School 03 Merigi Regency Kepahiang school year 2015/2016 in learning ability of speaking, and (2) How to change the behavior of fourth grade students Primary School 03 Years of Kepahiang Regency year teaching 2015/2016 in learning to speak after being given a learning by applying a role playing method.The purpose of this study is to describe the effort to improve the speaking skill and behavioral change of class IV students of Primary School 03 Merigi District Kepahiang Regency by learning to talk about application of role playing method. The variables in this study are the variables of improving the students' speaking skills. Data collection at the preliminary stage uses test techniques, while data collection at cycle 1 and cycle II uses test and nontes techniques. The results of the study were analyzed by quantitative and qualitative techniques.The result of this study shows that after the learning - learning method, the application of the class role of the fourth - grade class student of the Primary School of Primary School 03 Merigi Kepahiang Regency from the value of cycle I to cycle II up to cycle III increased. From the implementation of each cycle, the value is 41.35 in cycle I, and 62.65 in cycle II then 76.5 in cycle III. Improving student-speaking skills is also followed by changes in behavior and interest and student activity. From the results of the student-speaking skill study, it can be concluded that the ability of fourth grade elementary school students 03 Merigi District of Kepahiang Regency improved after following the learning process talking with the application of role playing method.